Transcriptome markers of viral persistence in naturally-infected Andes Hantavirus (Bunyaviridae) seropositive rice rats. Issue 4 (May 2015) - Campbell, Corey L.; Torres-Perez, Fernando; Acuna-Retamar, Mariana; Schountz, Tony
Abstract : The long-tailed pygmy rice rat ( Oligoryzomys longicaudatus ) is the reservoir host of Andes (ANDV) and Oran hantaviruses ( Bunyaviridae ). To examine transcriptome features of persistently infected rice rats, spleens from ANDV sero-positive wild-caught rice rats were assessed. RNA-seq analysis, de novo reference-independent assembly and stringent orthology assignments produced 17, 756 unique coding and non-coding RNAs. Differential expression analysis of persistently-infected seropositive rice rat spleens revealed 18 differentially expressed transcripts from 16 unique genes. A three-pronged effect on the immune response were observed in 1) suppression of the JAK-STAT pathway at Stat5b and Ccnot1, as well as 2) a bias toward a TH2 response in the enrichment of caspase-1 and 3) stimulation of RIG-I pathway factors Ppp1cc and MFF. Two of these differentially expressed transcripts, caspase-1 and STAT5b, code for proteins expected to stimulate T helper follicular (TFH ) cell development, a phenomenon that has also been described for hantavirus-infected P. maniculatus . Differential expression of a single seropositive rice rat with a higher viral load revealed a robust response of 243 differentially expressed transcripts, suggesting an acute infection. Together, these data help define the fundamental features of the immune response in a hantavirus reservoir host.